The times they are changing? : crisis and the welfare state - Greve, Bent (Broadening perspectives on social policy, 2012)
The Times They Are Changing? presents a series of readings that critically examine whether the recent financial crisis will have short-lived implications for welfare states or will usher in a new era of substantial reform and retrenchment of social policies in welfare states around the world